2004
DOI: 10.1021/tx049900+
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Predicting Acyl Glucuronide Reactivity via Schiff Base Formation:  Development of Rapidly Formed Peptide Adducts for LC/MS/MS Measurements

Abstract: A novel technique to study the reactivity of acyl glucuronide metabolites to protein has been developed and is described herein. Considered here are acyl glucuronide metabolites, which have undergone the rearrangement of the glucuronic acid moiety at physiological temperature and pH. The investigation of the reactivity of these electrophilic metabolites was carried out by measuring the rate of reaction of rearranged AG metabolites in forming the corresponding acyl glucuronide-peptide adduct in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 24 publications
4
72
0
Order By: Relevance
“…It was hypothesized that the benzoic acid derivative demonstrates the lowest reactivity due to resonance stabilization provided by the aromatic moiety, and the isopropionic acid derivative displays a lower reactivity than that of acetic acid derivative, possibly due to the higher steric hindrance capacity of the isopropyl group over the acetyl group (Wang et al, 2004). In our study, most AGs from the warning and withdrawn drugs are acetic acid or isopropionic acid derivatives except for furosemide AG, mefenamic acid AG, and probenecid AG.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It was hypothesized that the benzoic acid derivative demonstrates the lowest reactivity due to resonance stabilization provided by the aromatic moiety, and the isopropionic acid derivative displays a lower reactivity than that of acetic acid derivative, possibly due to the higher steric hindrance capacity of the isopropyl group over the acetyl group (Wang et al, 2004). In our study, most AGs from the warning and withdrawn drugs are acetic acid or isopropionic acid derivatives except for furosemide AG, mefenamic acid AG, and probenecid AG.…”
Section: Discussionmentioning
confidence: 58%
“…It was reported that a structure effect on the degree of AG reactivity demonstrated the rate order: acetic acid Ͼ isopropionic acid Ͼ benzoic acid derivatives in covalent binding study using a small peptide (Wang et al, 2004). It was hypothesized that the benzoic acid derivative demonstrates the lowest reactivity due to resonance stabilization provided by the aromatic moiety, and the isopropionic acid derivative displays a lower reactivity than that of acetic acid derivative, possibly due to the higher steric hindrance capacity of the isopropyl group over the acetyl group (Wang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Much attention has been drawn to the Schiff bases because of their potential applications in areas such as drugs, catalysis and supramolecular functional materials [1][2][3][4]. Schiff bases usually act as multi-dentate ligands in the construction of intriguing frameworks driven by coordination interactions [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Because of their electrophilic nature and ability to cause substitution reactions with nucleophilic groups in proteins or other macromolecules, AGs can covalently modify endogenous proteins and have been postulated to cause the adverse toxicity associated with carboxylic acid-containing drugs (Faed, 1984;Boelsterli, 2002). To assess the toxicity of AGs, several in vitro assay systems, such as stability assay by measuring half-lives in potassium phosphate buffer, peptide adducts assay, and immunostimulation assay, have been proposed (Wang et al, 2004;Sawamura et al, 2010;Jinno et al, 2013;Miyashita et al, 2014;Iwamura et al, 2015). However, the toxicity of AGs has remained controversial because direct evidence of in vivo AG toxicity has not been provided.…”
Section: Introductionmentioning
confidence: 99%